Emissions from Solid Fuel Cook Stoves in the Himalayan Region - Jin Dang (Energies, 2019)
Solid fuel cooking stoves have been used as primary energy sources for residential cooking and heating activities throughout human history. It has been estimated that domestic combustion of solid fuels makes a considerable contribution to global greenhouse gas (GHG) and pollutant emissions. The majority of data collected from simulated tests in laboratories does not accurately reflect the performance of stoves in actual use. This study characterizes in-field emissions of fine particulate matter (PM2.5), carbon dioxide (CO2), carbon monoxide (CO), methane (CH4), and total non-methane hydrocarbons (TNMHC) from residential cooking events with various fuel and stove types from villages in two provinces in China (Tibet and Yunnan) in the Himalayan area. Emissions of PM2.5 and gas-phase pollutant concentrations were measured directly and corresponding emission factors calculated using the carbon balance approach. Real-time monitoring of indoor PM2.5, CO2, and CO concentrations was conducted simultaneously. Major factors responsible for emission variance among and between cooking stoves are discussed.